Effect of lateral bone augmentation procedures in correcting peri‐implant bone dehiscence and fenestration defects: A systematic review and network meta‐analysis. (22nd March 2022) - Severi, Mattia; Simonelli, Anna; Farina, Roberto; Tu, Yu‐Kang; Lan, Cheng‐Hsiang; Shih, Ming‐Chieh; Trombelli, Leonardo
Abstract: Purpose: The aim of the present systematic review was to evaluate the effect of different lateral bone augmentation (LBA) procedures on the complete correction of a peri‐implant bone dehiscence (BD) or fenestration (BF) from implant placement to implant surgical uncovering. Methods: Electronic (Medline, Scopus, and Cochrane databases) and hand literature searches were performed for studies including at least one treatment arm where any LBA had been applied to correct a BD/BF at implant placement (T0). Studies where BD/BF was left untreated were also retrieved as negative control. Data from 24 selected articles were used to perform a network meta‐analysis. Based on the proportion of nonresolved BD/BF at implant surgical uncovering (T1), a hierarchy of LBA procedures, and was determined. Spontaneous healing (i.e., exposed implant surface covered by a full‐thickness flap; SELF) was also included in the hierarchy. Resorbable membrane + bone graft (RM + BG) was used as reference group. An analysis on the effect of nonhuman (NHBS) vs human (HBS) derived bone substitutes was also performed. NHBS was used as the reference group. Results: No statistically significant differences were found among treatments for the proportion of nonresolved BD/BF. SELF performed substantially worse compared to RM + BG (OR: 5.78 × 10, CI: 4.83 × 10 – 1.3 × 10 86 ). Treatment based on a combination of a graft material and membrane/periosteum appeared to perform slightly better than treatments using graft material or membrane alone. NHBS appeared to perform better than HBS. SELF had the worst effect among all treatments for both BD/BF height reduction (BDH) and BD/BF width reduction (BDW). Nonresorbable membrane (NRM) and patient's own periosteum (PERI) + BG showed greater increases in buccal bone thickness than RM + BG. Conclusion: Reconstructive treatment (including use of graft alone, membrane alone, or combinations of grafts and either membrane or patient's own periosteum) of a BD/BF at implant placement favorably and significantly impacts on the probability to obtain complete correction of the BD/BF at implant uncovering when compared to full‐thickness flap repositioning on the BD/BF. When using a bone substitute, a nonhuman derived one may be suggested.